A composite plastic based on PPO material and preparation method thereof

By introducing grafted modified polyphenylene ether, plasticized modified polyvinyl chloride, flame retardant hybrid particles and other components into PPO materials, the composite plastics are prepared by blending and preparing composite plastics, and the existing PPO materials are solved in weather resistance and flame retardant. The performance deficiency has achieved higher thermal stability and fire resistance.

CN118956137BActive Publication Date: 2025-02-07TELIFU PLASTICS (GUANGZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411215838.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-02-07
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The existing composite plastics based on PPO materials have insufficient weather resistance and flame retardant properties in certain specific environments.

Method used

The stable mechanical properties are prepared by melt blending grafted modified polyphenylene ether, plasticized modified polyvinyl chloride, flame retardant hybrid particles, modified fiber components, enhancing powders and silane coupling agents. and composite plastic with flame retardant properties.

Benefits of technology

The thermal stability, mechanical properties and flame retardant properties of composite plastics have been significantly improved, and they can maintain stability at high temperatures and have good fire resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and in particular to a composite plastic based on a PPO material and a preparation method thereof. The invention uses a polyphenylene ether having a chain-branched triazine group and polyvinyl chloride modified by a long-chain fatty acid ester as raw materials for blending, and can prepare a composite plastic with good thermal stability and plasticity; the triazine group is chain-branched on the polyphenylene ether side chain, and can significantly improve the thermal stability of the polyphenylene ether; the triazine group has excellent heat resistance and can maintain structural stability at high temperatures, so that the modified polyphenylene ether has a higher use temperature range; the introduction of the long-chain fatty acid ester can further improve the performance of the polyvinyl chloride at high temperatures; the prepared composite plastic can have good thermal stability through the combination of the two; the flexible characteristics of the long-chain fatty acid ester can adjust the toughness of the composite plastic, and combined with the rigidity of the modified polyphenylene ether, the rigidity and toughness of the composite plastic can be better balanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a composite plastic based on PPO material and a preparation method thereof. Background Art

[0002] PPO, or polyphenylene ether, is an important engineering plastic. It has been widely used in the fields of electronics, automobiles, machinery, aerospace, etc. due to its excellent mechanical properties, heat resistance, water resistance, chemical resistance and good electrical insulation. However, pure PPO materials still have shortcomings in some aspects, such as weather resistance and flame retardancy in certain specific environments, which need to be improved. Therefore, it is of great research significance and application value to develop composite plastics based on PPO materials and to overcome the shortcomings of pure PPO materials and improve their comprehensive performance through composite modification with other materials.

[0003] In the preparation process of PPO composite materials, it is very important to select appropriate composite components and preparation processes. For example, compounding PPO with liquid crystal polymers, polyethylene terephthalate, nylon, polyvinyl chloride and other polymer materials can significantly improve the mechanical properties and heat resistance of the material; adding reinforcing materials such as short glass fibers and inorganic fillers can effectively improve the rigidity and dimensional stability of the material; and introducing functional additives such as antioxidants and lubricants can improve the processing performance and long-term performance of the material. However, the performance of the prepared composite material will not be stable enough by simple blending modification. Therefore, it is necessary to improve the specific process of blending modification so that the prepared composite material has stable performance. Summary of the invention

[0004] Technical issues solved

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a composite plastic based on PPO material and a preparation method thereof, which can effectively solve the problem that the composite plastic in the prior art has stable mechanical properties and flame retardant properties.

[0006] Technical Solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A composite plastic based on PPO material, the composite plastic based on PPO material is composed of the following components: grafted modified polyphenylene ether, plasticized modified polyvinyl chloride, flame retardant hybrid particles, modified fiber components, enhanced powder and silane coupling agent;

[0009] The grafted modified polyphenylene ether is prepared by using polyphenylene ether as the main body and grafting triazine groups on its side chains;

[0010] The plasticized modified polyvinyl chloride is obtained by grafting and modifying polyvinyl chloride with long-chain fatty acid esters;

[0011] The flame retardant hybrid particles are prepared by using zinc sulfate heptahydrate and sodium stannate tetrahydrate as raw materials and then undergoing flame retardant modification;

[0012] The modified fiber component is prepared by modifying carbon fiber and glass fiber through dopamine.

[0013] Furthermore, the preparation steps of the graft modified polyphenylene ether are:

[0014] Step 2.1, weighing 1.3 g of N-bromosuccinimide and dissolving it in 50 mL of carbon tetrachloride as N-bromosuccinimide solution, then weighing 1 g of polyphenylene ether and dissolving it in 200 mL of carbon tetrachloride as polyphenylene ether solution, adding 0.015 g of azobisisobutyronitrile to the polyphenylene ether solution, heating it in a water bath to 70° C., and then dropping the N-bromosuccinimide solution after condensation and reflux, reacting for 12 h, adding 200 mL of deionized water, and filtering to obtain a filtered product;

[0015] Step 2.2, petroleum ether and ethyl acetate are mixed in an equal volume ratio to prepare a washing liquid, and the washing liquid is used to rinse the filtered product, and the obtained product is recorded as an intermediate product;

[0016] Step 2.3, weigh 1.3 g of the intermediate product and 1 g of 9-(4,6-diphenyl-1,3,5-triazine-2-yl)-9H-carbazole-3-ol, dissolve them in 200 mL of N,N-dimethylformamide, add 0.5 g of calcium carbonate and react under nitrogen protection for 24 hours. The solid product obtained after filtration is the grafted modified polyphenylene ether.

[0017] Furthermore, the preparation steps of the plasticized modified polyvinyl chloride are:

[0018] Step 3.1, methyl stearate and 1,3-propylenediamine were mixed in a molar ratio of 2:3 and recorded as a raw material component, 5-6 g of the raw material component was weighed and added into 100 mL of methanol, heated to 60° C. in a water bath and reacted at a constant temperature for 12 h, followed by reduced pressure distillation at 150° C. for 1 h, and the obtained product was recorded as a modifier component;

[0019] Step 3.2, weigh 1g of the modifier component and 30g of polyvinyl chloride and dissolve them in 100mL of N,N-dimethylformamide, heat to 80°C in a water bath and react at a constant temperature for 2h. After the reaction is completed, cool to room temperature and add 100mL of methanol to obtain flocs. Filter the flocs and then dissolve them in 100mL of tetrahydrofuran. Then add 100mL of methanol to precipitate the flocs. Filter them again and place them in an oven at 60°C to dry for 12h. The obtained product is plasticized modified polyvinyl chloride.

[0020] Furthermore, the preparation steps of the flame retardant hybrid particles are:

[0021] Step 4.1, weighing 0.6 g of zinc sulfate heptahydrate and dissolving it in 200 mL of deionized water, and magnetically stirring at a temperature of 5° C. to obtain a zinc sulfate heptahydrate solution, weighing 0.6 g of sodium stannate tetrahydrate and dissolving it in 50 mL of deionized water, stirring until completely dissolved, and then pouring it into the zinc sulfate heptahydrate solution, and reacting it in an ice water bath for 5 hours, then washing the filtered precipitate with anhydrous ethanol and deionized water three times each, and drying and grinding the obtained particles as hybrid particles;

[0022] Step 4.2, weigh 0.1g of azobisisobutyronitrile and dissolve it in 50mL of benzene solution, the result is recorded as the initiator component, 21g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 15g of vinyltrimethoxysilane and 100mL of benzene solution are poured into a flask, heated to 80°C under nitrogen protection, and stirred for reaction, then the initiator component is added dropwise and stirred at a temperature of 80°C and a stirring speed of 300r / min for 24h, the product is filtered through a Buchner funnel to remove the filtrate and then subjected to rotary evaporation, and the product is recorded as a flame retardant component;

[0023] Step 4.3, disperse 3-5g of hybrid particles in 100mL of 60% ethanol aqueous solution, add 7mL of flame retardant component and stir at 500r / min until dissolved, then heat to 80℃ and keep the reaction at constant temperature for 6h. After filtration, the obtained precipitate is rinsed 3 times with deionized water, and the obtained flame retardant hybrid particles are obtained after drying and grinding.

[0024] Furthermore, in step 4.1, the specific operation of magnetic stirring is stirring at a stirring speed of 500 r / min for 10 min, the specific operation of stirring until complete dissolution is stirring at a stirring speed of 300 r / min for 10 min, and the specific operation of dry grinding is placing in an oven at 65° C. for 5-6 h and then grinding through a 200 mesh sieve.

[0025] Furthermore, in step 4.2, the specific operation of the stirring reaction is stirring at a stirring speed of 300 r / min for 10 min and a dripping rate of 1 drop / s, the specific operation of the rotary evaporation treatment is rotary evaporation at a rotary evaporation temperature of 68°C for 30 min, and in step 4.3, the specific operation of the drying and grinding treatment is drying in an oven at 65°C for 4-5h and then grinding through a 200 mesh sieve.

[0026] Furthermore, the preparation steps of the modified fiber component are:

[0027] Step 7.1, adding 2 g of dopamine hydrochloride to a Tris solution having a concentration of 0.01 mol / L, stirring at a stirring speed of 300 r / min for 10 min, and the resultant solution is recorded as dopamine hydrochloride-Tris solution;

[0028] Step 7.2, the carbon fiber and the glass fiber are mixed in an equal weight ratio and recorded as a mixed fiber, and the ethanol and acetone are mixed in an equal volume ratio and recorded as a mixed solution, and the mixed fiber is immersed in the mixed solution for 24 hours, and after being taken out, it is rinsed with deionized water for 3 times and then placed in an oven at 65° C. for 2-3 hours, and the obtained fiber is recorded as the fiber to be modified;

[0029] Step 7.3, immerse the modified fiber in a dopamine hydrochloride-Tris solution for 16 hours, take it out, rinse it with deionized water for 3 times, and then dry it in an oven at 65° C. for 2-3 hours. The result is the modified fiber component.

[0030] Furthermore, the enhanced powder is prepared by mixing nano silicon dioxide, nano titanium dioxide, aluminum oxide and calcium carbonate in equal weight ratios.

[0031] A method for preparing a composite plastic based on PPO material, the preparation method comprising:

[0032] Weigh 7-8 parts by weight of flame retardant hybrid particles, 12-15 parts by weight of modified fiber components, 5-6 parts by weight of enhanced powder and 15-18 parts by weight of silane coupling agent and pour them into a ball mill. The ball milling result is recorded as the ball milling component. Weigh 65-80 parts by weight of grafted modified polyphenylene ether, 35-50 parts by weight of plasticized modified polyvinyl chloride and the above ball milling component and pour them into a mixer for melt blending to obtain a composite plastic based on PPO material.

[0033] Furthermore, the ball milling speed is 600 r / min, and the ball milling time is 30 min.

[0034] Beneficial Effects

[0035] The present invention provides a composite plastic based on PPO material and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The present invention uses polyphenylene ether with chain-branched triazine groups and polyvinyl chloride modified by long-chain fatty acid esters as raw materials for blending, and can prepare a composite plastic with good thermal stability and plasticity; the triazine groups are chain-branched on the polyphenylene ether side chain, which can significantly improve the thermal stability of the polyphenylene ether. The triazine groups have excellent heat resistance and can maintain structural stability at high temperatures, so that the modified polyphenylene ether has a higher operating temperature range, and the introduction of long-chain fatty acid esters can further improve the performance of polyvinyl chloride at high temperatures. The prepared composite plastic can have good thermal stability through the combination of the two. Secondly, the triazine groups in the modified polyphenylene ether can interact with the groups in the modified polyvinyl chloride to form a stronger interface bond, thereby improving the overall mechanical properties of the composite plastic, and the flexible characteristics of the long-chain fatty acid esters can adjust the toughness of the composite plastic, and combined with the rigidity of the modified polyphenylene ether, the rigidity and toughness of the composite plastic can be better balanced.

[0037] 2. The present invention uses zinc sulfate heptahydrate and sodium stannate tetrahydrate as raw materials to prepare hybrid particles, which are then flame-retardant modified by 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and then added to the composite plastic. The flame retardant properties of the composite plastic can be improved on the basis of improving the mechanical properties of the composite plastic by the hybrid particles. The introduction of the hybrid particles may help to improve the dispersibility and compatibility of the flame retardant in the composite plastic, reduce agglomeration, and improve the processing performance of the plastic. Secondly, in the present invention, after the surface of the carbon fiber and the glass fiber is modified by dopamine, a uniform polydopamine film can be formed. This film not only increases the roughness of the fiber surface, but also introduces abundant amino and hydroxyl functional groups, thereby significantly improving the interface compatibility between the fiber and the plastic matrix. Moreover, the adhesion and reactivity of the polydopamine film enable the fiber and the matrix to form a stronger chemical bond connection, which can enhance the interface bonding strength of the composite plastic. The tight bonding between the modified fiber and the matrix enables the composite plastic to better transfer the load when subjected to external force, thereby improving the tensile and bending strength of the composite plastic. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The present invention will be further described below in conjunction with the embodiments.

[0040] Example 1

[0041] A composite plastic based on PPO material in this embodiment, the composite plastic based on PPO material is composed of the following components: grafted modified polyphenylene ether, plasticized modified polyvinyl chloride, flame retardant hybrid particles, modified fiber components, enhanced powder and silane coupling agent;

[0042] The graft modified polyphenylene ether is prepared by grafting triazine groups on its side chains with polyphenylene ether as the main body. The preparation steps of the graft modified polyphenylene ether are as follows:

[0043] Step 2.1, weighing 1.3 g of N-bromosuccinimide and dissolving it in 50 mL of carbon tetrachloride as N-bromosuccinimide solution, then weighing 1 g of polyphenylene ether and dissolving it in 200 mL of carbon tetrachloride as polyphenylene ether solution, adding 0.015 g of azobisisobutyronitrile to the polyphenylene ether solution, heating it in a water bath to 70° C., and then dropping the N-bromosuccinimide solution after condensation and reflux, reacting for 12 h, adding 200 mL of deionized water, and filtering to obtain a filtered product;

[0044] Step 2.2, petroleum ether and ethyl acetate are mixed in an equal volume ratio to prepare a washing liquid, and the washing liquid is used to rinse the filtered product, and the obtained product is recorded as an intermediate product;

[0045] Step 2.3, weigh 1.3 g of the intermediate product and 1 g of 9-(4,6-diphenyl-1,3,5-triazine-2-yl)-9H-carbazole-3-ol, dissolve them in 200 mL of N,N-dimethylformamide, add 0.5 g of calcium carbonate and react under nitrogen protection for 24 hours. The solid product obtained after filtration is the grafted modified polyphenylene ether.

[0046] Plasticized modified polyvinyl chloride is prepared by grafting polyvinyl chloride with long-chain fatty acid esters. The preparation steps of plasticized modified polyvinyl chloride are as follows:

[0047] Step 3.1, methyl stearate and 1,3-propylenediamine were mixed in a molar ratio of 2:3 and recorded as a raw material component, 5 g of the raw material component was weighed and added into 100 mL of methanol, heated to 60° C. in a water bath and reacted at a constant temperature for 12 h, followed by reduced pressure distillation at 150° C. for 1 h, and the obtained product was recorded as a modifier component;

[0048] Step 3.2, weigh 1g of the modifier component and 30g of polyvinyl chloride and dissolve them in 100mL of N,N-dimethylformamide, heat to 80°C in a water bath and react at a constant temperature for 2h. After the reaction is completed, cool to room temperature and add 100mL of methanol to obtain flocs. Filter the flocs and then dissolve them in 100mL of tetrahydrofuran. Then add 100mL of methanol to precipitate the flocs. Filter them again and place them in an oven at 60°C to dry for 12h. The obtained product is plasticized modified polyvinyl chloride.

[0049] The flame retardant hybrid particles are prepared by using zinc sulfate heptahydrate and sodium stannate tetrahydrate as raw materials and then being flame retardant modified. The preparation steps of the flame retardant hybrid particles are as follows:

[0050] Step 4.1, weighing 0.6 g of zinc sulfate heptahydrate and dissolving it in 200 mL of deionized water, stirring at a temperature of 5° C. and a stirring speed of 500 r / min for 10 min to obtain a zinc sulfate heptahydrate solution, weighing 0.6 g of sodium stannate tetrahydrate and dissolving it in 50 mL of deionized water, stirring at a stirring speed of 300 r / min for 10 min, then pouring it into the zinc sulfate heptahydrate solution, and reacting it in an ice water bath for 5 h, then washing the filtered precipitate with anhydrous ethanol and deionized water for 3 times each, placing it in an oven at 65° C. and drying it for 5 h, and then grinding it through a 200-mesh sieve to obtain the hybrid particles;

[0051] Step 4.2, weigh 0.1g of azobisisobutyronitrile and dissolve it in 50mL of benzene solution, the result is recorded as the initiator component, 21g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 15g of vinyltrimethoxysilane and 100mL of benzene solution are poured into a flask, heated to 80°C under nitrogen protection, and stirred at a stirring speed of 300r / min for 10min, then the initiator component is added dropwise at a drip rate of 1 drop / s and stirred at a temperature of 80°C at a stirring speed of 300r / min for 24h, the product is filtered through a Buchner funnel to remove the filtrate, and then rotary evaporated at a rotary evaporation temperature of 68°C for 30mi, and the product is recorded as a flame retardant component;

[0052] Step 4.3, disperse 3 g of hybrid particles in 100 mL of 60% ethanol aqueous solution, add 7 mL of flame retardant component and stir at 500 r / min until dissolved, then heat to 80 ° C and react at a constant temperature for 6 hours. After filtration, the obtained precipitate is rinsed with deionized water three times, placed in an oven at 65 ° C for 4 hours, and then ground through a 200-mesh sieve to obtain flame retardant hybrid particles.

[0053] The modified fiber component is prepared by modifying carbon fiber and glass fiber by dopamine. The preparation steps of the modified fiber component are as follows:

[0054] Step 7.1, adding 2 g of dopamine hydrochloride to a Tris solution having a concentration of 0.01 mol / L, stirring at a stirring speed of 300 r / min for 10 min, and the resultant solution is recorded as dopamine hydrochloride-Tris solution;

[0055] Step 7.2, the carbon fiber and the glass fiber are mixed in an equal weight ratio and recorded as a mixed fiber, and the ethanol and acetone are mixed in an equal volume ratio and recorded as a mixed solution, and the mixed fiber is immersed in the mixed solution for 24 hours, and after being taken out, it is rinsed with deionized water for 3 times and then placed in an oven at 65° C. for 2 hours, and the obtained fiber is recorded as the fiber to be modified;

[0056] Step 7.3, immerse the modified fiber in a dopamine hydrochloride-Tris solution for 16 hours, take it out, rinse it with deionized water for 3 times, and then dry it in an oven at 65° C. for 2 hours. The result is the modified fiber component.

[0057] The enhanced powder is prepared by mixing nano silicon dioxide, nano titanium dioxide, aluminum oxide and calcium carbonate in equal weight ratios.

[0058] A method for preparing a composite plastic based on PPO material, the preparation method comprising:

[0059] Weigh 7 parts by weight of flame-retardant hybrid particles, 12 parts by weight of modified fiber components, 5 parts by weight of enhancing powder and 15 parts by weight of silane coupling agent, pour them into a ball mill, and mill them at a speed of 600 r / min for 30 minutes, and record the result as the ball-milled component. Weigh 65 parts by weight of grafted modified polyphenylene ether, 35 parts by weight of plasticized modified polyvinyl chloride and the above-mentioned ball-milled component into a mixer for melt blending, and the result is a composite plastic based on PPO material.

[0060] Example 2

[0061] A composite plastic based on PPO material in this embodiment, the composite plastic based on PPO material is composed of the following components: grafted modified polyphenylene ether, plasticized modified polyvinyl chloride, flame retardant hybrid particles, modified fiber components, enhanced powder and silane coupling agent;

[0062] The graft modified polyphenylene ether is prepared by grafting triazine groups on its side chains with polyphenylene ether as the main body. The preparation steps of the graft modified polyphenylene ether are as follows:

[0063] Step 2.1, weighing 1.3 g of N-bromosuccinimide and dissolving it in 50 mL of carbon tetrachloride as N-bromosuccinimide solution, then weighing 1 g of polyphenylene ether and dissolving it in 200 mL of carbon tetrachloride as polyphenylene ether solution, adding 0.015 g of azobisisobutyronitrile to the polyphenylene ether solution, heating it in a water bath to 70° C., and then dropping the N-bromosuccinimide solution after condensation and reflux, reacting for 12 h, adding 200 mL of deionized water, and filtering to obtain a filtered product;

[0064] Step 2.2, petroleum ether and ethyl acetate are mixed in an equal volume ratio to prepare a washing liquid, and the washing liquid is used to rinse the filtered product, and the obtained product is recorded as an intermediate product;

[0065] Step 2.3, weigh 1.3 g of the intermediate product and 1 g of 9-(4,6-diphenyl-1,3,5-triazine-2-yl)-9H-carbazole-3-ol, dissolve them in 200 mL of N,N-dimethylformamide, add 0.5 g of calcium carbonate and react under nitrogen protection for 24 hours. The solid product obtained after filtration is the grafted modified polyphenylene ether.

[0066] Plasticized modified polyvinyl chloride is prepared by grafting polyvinyl chloride with long-chain fatty acid esters. The preparation steps of plasticized modified polyvinyl chloride are as follows:

[0067] Step 3.1, methyl stearate and 1,3-propylenediamine were mixed in a molar ratio of 2:3 and recorded as a raw material component, 6 g of the raw material component was weighed and added into 100 mL of methanol, heated to 60° C. in a water bath and reacted at a constant temperature for 12 h, followed by reduced pressure distillation at a temperature of 150° C. for 1 h, and the obtained product was recorded as a modifier component;

[0068] Step 3.2, weigh 1g of the modifier component and 30g of polyvinyl chloride and dissolve them in 100mL of N,N-dimethylformamide, heat to 80°C in a water bath and react at a constant temperature for 2h. After the reaction is completed, cool to room temperature and add 100mL of methanol to obtain flocs. Filter the flocs and then dissolve them in 100mL of tetrahydrofuran. Then add 100mL of methanol to precipitate the flocs. Filter them again and place them in an oven at 60°C to dry for 12h. The obtained product is plasticized modified polyvinyl chloride.

[0069] The flame retardant hybrid particles are prepared by using zinc sulfate heptahydrate and sodium stannate tetrahydrate as raw materials and then being flame retardant modified. The preparation steps of the flame retardant hybrid particles are as follows:

[0070] Step 4.1, weighing 0.6 g of zinc sulfate heptahydrate and dissolving it in 200 mL of deionized water, stirring at a temperature of 5° C. and a stirring speed of 500 r / min for 10 min to obtain a zinc sulfate heptahydrate solution, weighing 0.6 g of sodium stannate tetrahydrate and dissolving it in 50 mL of deionized water, stirring at a stirring speed of 300 r / min for 10 min, then pouring it into the zinc sulfate heptahydrate solution, and reacting it in an ice water bath for 5 h, then washing the filtered precipitate with anhydrous ethanol and deionized water 3 times each, placing it in an oven at 65° C. and drying it for 6 h, and then grinding it through a 200-mesh sieve to obtain the hybrid particles;

[0071] Step 4.2, weigh 0.1g of azobisisobutyronitrile and dissolve it in 50mL of benzene solution, the result is recorded as the initiator component, 21g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 15g of vinyltrimethoxysilane and 100mL of benzene solution are poured into a flask, heated to 80°C under nitrogen protection, and stirred at a stirring speed of 300r / min for 10min, then the initiator component is added dropwise at a drip rate of 1 drop / s and stirred at a temperature of 80°C at a stirring speed of 300r / min for 24h, the product is filtered through a Buchner funnel to remove the filtrate, and then rotary evaporated at a rotary evaporation temperature of 68°C for 30mi, and the product is recorded as a flame retardant component;

[0072] Step 4.3, disperse 5 g of hybrid particles in 100 mL of 60% ethanol aqueous solution, add 7 mL of flame retardant component and stir at 500 r / min until dissolved, then heat to 80 ° C and react at a constant temperature for 6 hours. After filtration, the obtained precipitate is rinsed with deionized water three times, placed in an oven at 65 ° C for 5 hours, and then ground through a 200-mesh sieve to obtain flame retardant hybrid particles.

[0073] The modified fiber component is prepared by modifying carbon fiber and glass fiber by dopamine. The preparation steps of the modified fiber component are as follows:

[0074] Step 7.1, adding 2 g of dopamine hydrochloride to a Tris solution having a concentration of 0.01 mol / L, stirring at a stirring speed of 300 r / min for 10 min, and the resultant solution is recorded as dopamine hydrochloride-Tris solution;

[0075] Step 7.2, the carbon fiber and the glass fiber are mixed in an equal weight ratio and recorded as a mixed fiber, and the ethanol and acetone are mixed in an equal volume ratio and recorded as a mixed solution, and the mixed fiber is immersed in the mixed solution for 24 hours, and after being taken out, it is rinsed with deionized water for 3 times and then placed in an oven at 65° C. for 3 hours, and the obtained fiber is recorded as the fiber to be modified;

[0076] Step 7.3, immerse the modified fiber in a dopamine hydrochloride-Tris solution for 16 hours, take it out, rinse it with deionized water for 3 times, and then dry it in an oven at 65° C. for 3 hours. The result is the modified fiber component.

[0077] The enhanced powder is prepared by mixing nano silicon dioxide, nano titanium dioxide, aluminum oxide and calcium carbonate in equal weight ratios.

[0078] A method for preparing a composite plastic based on PPO material, the preparation method comprising:

[0079] Weigh 8 parts by weight of flame retardant hybrid particles, 15 parts by weight of modified fiber components, 6 parts by weight of enhancing powder and 18 parts by weight of silane coupling agent, pour them into a ball mill, and ball mill them at a speed of 600 r / min for 30 minutes, and record the result as the ball-milled component. Weigh 80 parts by weight of grafted modified polyphenylene ether, 50 parts by weight of plasticized modified polyvinyl chloride and the above-mentioned ball-milled component into a mixer for melt blending, and the result is a composite plastic based on PPO material.

[0080] Example 3

[0081] A composite plastic based on PPO material in this embodiment, the composite plastic based on PPO material is composed of the following components: grafted modified polyphenylene ether, plasticized modified polyvinyl chloride, flame retardant hybrid particles, modified fiber components, enhanced powder and silane coupling agent;

[0082] The graft modified polyphenylene ether is prepared by grafting triazine groups on its side chains with polyphenylene ether as the main body. The preparation steps of the graft modified polyphenylene ether are as follows:

[0083] Step 2.1, weighing 1.3 g of N-bromosuccinimide and dissolving it in 50 mL of carbon tetrachloride as N-bromosuccinimide solution, then weighing 1 g of polyphenylene ether and dissolving it in 200 mL of carbon tetrachloride as polyphenylene ether solution, adding 0.015 g of azobisisobutyronitrile to the polyphenylene ether solution, heating it in a water bath to 70° C., and then dropping the N-bromosuccinimide solution after condensation and reflux, reacting for 12 h, adding 200 mL of deionized water, and filtering to obtain a filtered product;

[0084] Step 2.2, petroleum ether and ethyl acetate are mixed in an equal volume ratio to prepare a washing liquid, and the washing liquid is used to rinse the filtered product, and the obtained product is recorded as an intermediate product;

[0085] Step 2.3, weigh 1.3 g of the intermediate product and 1 g of 9-(4,6-diphenyl-1,3,5-triazine-2-yl)-9H-carbazole-3-ol, dissolve them in 200 mL of N,N-dimethylformamide, add 0.5 g of calcium carbonate and react under nitrogen protection for 24 hours. The solid product obtained after filtration is the grafted modified polyphenylene ether.

[0086] Plasticized modified polyvinyl chloride is prepared by grafting polyvinyl chloride with long-chain fatty acid esters. The preparation steps of plasticized modified polyvinyl chloride are as follows:

[0087] Step 3.1, methyl stearate and 1,3-propylenediamine were mixed in a molar ratio of 2:3 and recorded as a raw material component, 6 g of the raw material component was weighed and added into 100 mL of methanol, heated to 60° C. in a water bath and reacted at a constant temperature for 12 h, followed by reduced pressure distillation at a temperature of 150° C. for 1 h, and the obtained product was recorded as a modifier component;

[0088] Step 3.2, weigh 1g of the modifier component and 30g of polyvinyl chloride and dissolve them in 100mL of N,N-dimethylformamide, heat to 80°C in a water bath and react at a constant temperature for 2h. After the reaction is completed, cool to room temperature and add 100mL of methanol to obtain flocs. Filter the flocs and then dissolve them in 100mL of tetrahydrofuran. Then add 100mL of methanol to precipitate the flocs. Filter them again and place them in an oven at 60°C to dry for 12h. The obtained product is plasticized modified polyvinyl chloride.

[0089] The flame retardant hybrid particles are prepared by using zinc sulfate heptahydrate and sodium stannate tetrahydrate as raw materials and then being flame retardant modified. The preparation steps of the flame retardant hybrid particles are as follows:

[0090] Step 4.1, weighing 0.6 g of zinc sulfate heptahydrate and dissolving it in 200 mL of deionized water, stirring at a temperature of 5° C. and a stirring speed of 500 r / min for 10 min to obtain a zinc sulfate heptahydrate solution, weighing 0.6 g of sodium stannate tetrahydrate and dissolving it in 50 mL of deionized water, stirring at a stirring speed of 300 r / min for 10 min, then pouring it into the zinc sulfate heptahydrate solution, and reacting it in an ice water bath for 5 h, then washing the filtered precipitate with anhydrous ethanol and deionized water 3 times each, placing it in an oven at 65° C. and drying it for 6 h, and then grinding it through a 200-mesh sieve to obtain the hybrid particles;

[0091] Step 4.2, weigh 0.1g of azobisisobutyronitrile and dissolve it in 50mL of benzene solution, the result is recorded as the initiator component, 21g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 15g of vinyltrimethoxysilane and 100mL of benzene solution are poured into a flask, heated to 80°C under nitrogen protection, and stirred at a stirring speed of 300r / min for 10min, then the initiator component is added dropwise at a drip rate of 1 drop / s and stirred at a temperature of 80°C at a stirring speed of 300r / min for 24h, the product is filtered through a Buchner funnel to remove the filtrate, and then rotary evaporated at a rotary evaporation temperature of 68°C for 30mi, and the product is recorded as a flame retardant component;

[0092] Step 4.3, disperse 4 g of hybrid particles in 100 mL of 60% ethanol aqueous solution, add 7 mL of flame retardant component and stir at 500 r / min until dissolved, then heat to 80 ° C and react at a constant temperature for 6 hours. After filtration, the obtained precipitate is rinsed with deionized water three times, placed in an oven at 65 ° C for 5 hours, and then ground through a 200-mesh sieve to obtain flame retardant hybrid particles.

[0093] The modified fiber component is prepared by modifying carbon fiber and glass fiber by dopamine. The preparation steps of the modified fiber component are as follows:

[0094] Step 7.1, adding 2 g of dopamine hydrochloride to a Tris solution having a concentration of 0.01 mol / L, stirring at a stirring speed of 300 r / min for 10 min, and the resultant solution is recorded as dopamine hydrochloride-Tris solution;

[0095] Step 7.2, the carbon fiber and the glass fiber are mixed in an equal weight ratio and recorded as a mixed fiber, and the ethanol and acetone are mixed in an equal volume ratio and recorded as a mixed solution, and the mixed fiber is immersed in the mixed solution for 24 hours, and after being taken out, it is rinsed with deionized water for 3 times and then placed in an oven at 65° C. for 3 hours, and the obtained fiber is recorded as the fiber to be modified;

[0096] Step 7.3, immerse the modified fiber in a dopamine hydrochloride-Tris solution for 16 hours, take it out, rinse it with deionized water for 3 times, and then dry it in an oven at 65° C. for 2 hours. The result is the modified fiber component.

[0097] The enhanced powder is prepared by mixing nano silicon dioxide, nano titanium dioxide, aluminum oxide and calcium carbonate in equal weight ratios.

[0098] A method for preparing a composite plastic based on PPO material, the preparation method comprising:

[0099] Weigh 7 parts by weight of flame retardant hybrid particles, 14 parts by weight of modified fiber components, 6 parts by weight of enhancing powder and 17 parts by weight of silane coupling agent, pour them into a ball mill, and ball mill them at a speed of 600 r / min for 30 minutes, and record the result as the ball-milled component. Weigh 68 parts by weight of grafted modified polyphenylene ether, 42 parts by weight of plasticized modified polyvinyl chloride and the above-mentioned ball-milled component into a mixer for melt blending, and the result is a composite plastic based on PPO material.

[0100] Comparative Example 1

[0101] The composite plastic based on PPO material and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the grafted modified polyphenylene ether in Example 1 is replaced by polyphenylene ether.

[0102] Comparative Example 2

[0103] The composite plastic based on PPO material and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the flame retardant hybrid particles in Example 1 are replaced with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0104] Comparative Example 3

[0105] The composite plastic based on PPO material and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the modified fiber component in Example 1 is replaced with carbon fiber.

[0106] Performance Testing

[0107] The composite plastics based on PPO materials prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-3 is tested. The specific testing methods and test items are as follows:

[0108] 1. The tensile properties of Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard of GB / T1040.3-2006, at a tensile rate of 50 mm / min. The obtained data are recorded in the following table;

[0109] 2. In a nitrogen atmosphere, the temperature was raised to 500° C. at a heating rate of 10° C. / min, and the mass retention rates of Examples 1-3 and Comparative Examples 1-3 were tested. The obtained data are recorded in the following table;

[0110] 3. The impact properties of Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard of GB / T1843-2008, and the obtained data are recorded in the following table;

[0111] 4. The limiting oxygen index of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of GB / T2406.1-2008, and the obtained data are recorded in the following table.

[0112]

[0113] It can be seen from the data in the above table that the tensile strength and impact strength of the composite plastics based on PPO materials in Examples 1-3 are significantly higher than those in Comparative Example 1 and Comparative Example 3, indicating that the grafted modified polyphenylene ether and modified fiber components added in the preparation of the composite plastics based on PPO materials can significantly improve the mechanical properties and mechanical properties of the composite plastics; secondly, the 500°C mass retention rate of the composite plastics based on PPO materials in Examples 1-3 is significantly higher than that in Comparative Example 1, indicating that the addition of grafted modified polyphenylene ether can improve the thermal stability of the composite plastics; finally, the limiting oxygen index of the composite plastics based on PPO materials in Examples 1-3 is significantly higher than that in Comparative Example 2, indicating that the addition of flame-retardant hybrid particles can achieve more excellent flame retardant properties compared to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0114] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0115] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite plastic based on PPO material, characterized in that: The composite plastic based on PPO material is composed of the following components: 65-80 parts by weight of grafted modified polyphenylene ether, 35-50 parts by weight of plasticized modified polyvinyl chloride, 7-8 parts by weight of flame retardant hybrid particles, 12-15 parts by weight of modified fiber components, 5-6 parts by weight of enhanced powder and 15-18 parts by weight of silane coupling agent; The grafted modified polyphenylene ether is prepared by using polyphenylene ether as the main body and grafting triazine groups on its side chains; The plasticized modified polyvinyl chloride is obtained by grafting and modifying polyvinyl chloride with long-chain fatty acid esters; The flame retardant hybrid particles are prepared by using zinc sulfate heptahydrate and sodium stannate tetrahydrate as raw materials and then undergoing flame retardant modification; The modified fiber component is prepared by modifying carbon fiber and glass fiber with dopamine; The preparation steps of the flame retardant hybrid particles are: Step 4.1, weighing 0.6 g of zinc sulfate heptahydrate and dissolving it in 200 mL of deionized water, and magnetically stirring at a temperature of 5° C. to obtain a zinc sulfate heptahydrate solution, weighing 0.6 g of sodium stannate tetrahydrate and dissolving it in 50 mL of deionized water, stirring until completely dissolved, and then pouring it into the zinc sulfate heptahydrate solution, and reacting it in an ice water bath for 5 hours, then washing the filtered precipitate with anhydrous ethanol and deionized water three times each, and drying and grinding the obtained particles as hybrid particles; Step 4.2, weigh 0.1g of azobisisobutyronitrile and dissolve it in 50mL of benzene solution, the result is recorded as the initiator component, 21g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 15g of vinyltrimethoxysilane and 100mL of benzene solution are poured into a flask, heated to 80°C under nitrogen protection, and stirred for reaction, then the initiator component is added dropwise and stirred at a temperature of 80°C and a stirring speed of 300r / min for 24h, the product is filtered through a Buchner funnel to remove the filtrate and then subjected to rotary evaporation, and the product is recorded as a flame retardant component; Step 4.3, 3-5 g of hybrid particles are dispersed in 100 mL of 60% ethanol aqueous solution, 7 mL of flame retardant component is added, and the mixture is stirred at a stirring speed of 500 r / min until dissolved, and then heated to 80°C and kept at a constant temperature for 6 hours. The obtained precipitate is filtered and rinsed with deionized water for 3 times, and the flame retardant hybrid particles are obtained after drying and grinding; The enhanced powder is prepared by mixing nano silicon dioxide, nano titanium dioxide, aluminum oxide and calcium carbonate in equal weight ratios.

2. A composite plastic based on PPO material according to claim 1, characterized in that: The preparation steps of the graft modified polyphenylene ether are: Step 2.1, weighing 1.3 g of N-bromosuccinimide and dissolving it in 50 mL of carbon tetrachloride as N-bromosuccinimide solution, then weighing 1 g of polyphenylene ether and dissolving it in 200 mL of carbon tetrachloride as polyphenylene ether solution, adding 0.015 g of azobisisobutyronitrile to the polyphenylene ether solution, heating it in a water bath to 70° C., and then dropping the N-bromosuccinimide solution after condensation and reflux, reacting for 12 h, adding 200 mL of deionized water, and filtering to obtain a filtered product; Step 2.2, petroleum ether and ethyl acetate are mixed in an equal volume ratio to prepare a washing liquid, and the washing liquid is used to rinse the filtered product, and the obtained product is recorded as an intermediate product; Step 2.3, weigh 1.3 g of the intermediate product and 1 g of 9-(4,6-diphenyl-1,3,5-triazine-2-yl)-9H-carbazole-3-ol, dissolve them in 200 mL of N,N-dimethylformamide, add 0.5 g of calcium carbonate and react under nitrogen protection for 24 hours. The solid product obtained after filtration is the grafted modified polyphenylene ether.

3. A composite plastic based on PPO material according to claim 1, characterized in that: The preparation steps of the plasticized modified polyvinyl chloride are: Step 3.1, methyl stearate and 1,3-propylenediamine were mixed in a molar ratio of 2:3 and recorded as a raw material component, 5-6 g of the raw material component was weighed and added into 100 mL of methanol, heated to 60° C. in a water bath and reacted at a constant temperature for 12 h, followed by reduced pressure distillation at 150° C. for 1 h, and the obtained product was recorded as a modifier component; Step 3.2, weigh 1g of the modifier component and 30g of polyvinyl chloride and dissolve them in 100mL of N,N-dimethylformamide, heat to 80°C in a water bath and react at a constant temperature for 2h. After the reaction is completed, cool to room temperature and add 100mL of methanol to obtain flocs. Filter the flocs and then dissolve them in 100mL of tetrahydrofuran. Then add 100mL of methanol to precipitate the flocs. Filter them again and place them in an oven at 60°C to dry for 12h. The obtained product is plasticized modified polyvinyl chloride.

4. A composite plastic based on PPO material according to claim 1, characterized in that: In step 4.1, the specific operation of magnetic stirring is stirring at a stirring speed of 500 r / min for 10 min, the specific operation of stirring until complete dissolution is stirring at a stirring speed of 300 r / min for 10 min, and the specific operation of dry grinding is placing in an oven at 65° C. for 5-6 h and then grinding through a 200 mesh sieve.

5. The composite plastic based on PPO material according to claim 1, characterized in that: In step 4.2, the specific operation of the stirring reaction is stirring at a stirring speed of 300 r / min for 10 min and a dripping rate of 1 drop / s. The specific operation of the rotary evaporation treatment is rotary evaporation at a rotary evaporation temperature of 68°C for 30 min. In step 4.3, the specific operation of the drying and grinding treatment is drying in an oven at 65°C for 4-5 hours and then grinding through a 200-mesh sieve.

6. The composite plastic based on PPO material according to claim 1, characterized in that: The preparation steps of the modified fiber component are: Step 7.1, adding 2 g of dopamine hydrochloride to a Tris solution having a concentration of 0.01 mol / L, stirring at a stirring speed of 300 r / min for 10 min, and the resultant solution is recorded as dopamine hydrochloride-Tris solution; Step 7.2, the carbon fiber and the glass fiber are mixed in an equal weight ratio and recorded as a mixed fiber, and the ethanol and acetone are mixed in an equal volume ratio and recorded as a mixed solution, and the mixed fiber is immersed in the mixed solution for 24 hours, and after being taken out, it is rinsed with deionized water for 3 times and then placed in an oven at 65° C. for 2-3 hours, and the obtained fiber is recorded as the fiber to be modified; Step 7.3, immerse the modified fiber in a dopamine hydrochloride-Tris solution for 16 hours, take it out, rinse it with deionized water for 3 times, and then dry it in an oven at 65° C. for 2-3 hours. The result is the modified fiber component.

7. A method for preparing a composite plastic based on PPO material according to any one of claims 1 to 6, characterized in that: The preparation method is: Weigh 7-8 parts by weight of flame retardant hybrid particles, 12-15 parts by weight of modified fiber components, 5-6 parts by weight of enhanced powder and 15-18 parts by weight of silane coupling agent and pour them into a ball mill. The ball milling result is recorded as the ball milling component. Weigh 65-80 parts by weight of grafted modified polyphenylene ether, 35-50 parts by weight of plasticized modified polyvinyl chloride and the above ball milling component and pour them into a mixer for melt blending to obtain a composite plastic based on PPO material.

8. The method for preparing a composite plastic based on PPO material according to claim 7, characterized in that: The ball milling speed is 600 r / min, and the ball milling time is 30 min.

Citation Information

Patent Citations

  • Shockproof conductive polyphenyl ether compound and method for making same

    CN101134840A

  • Polyvinyl chloride modified polyphenylene oxide material for automobile plastic parts

    CN103937203A